Implementasi Metode Scrum Dalam Rancang Bangun Sistem Informasi Penjualan (Study Kasus : Penjualan Sperpart Kendaraan) - Novri Hadinata; Muhammad Nasir (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
The process of processing sales data and inventory items recorded in a file in the form of sheets of paper, where the data will be stored on the archive biling. Besides this company is also difficult to determine the stock of goods in the warehouse, so often the occurrence of accumulation and lack of car spare parts due to unstable storage. Sales process where the system is designed by applying a method that is Scrum method where this method contains many sprint and workload which each sprint driven by Prioritized product backlog. Prioritized Product Backlog consists of the latest features, bug fixes, and anything else that contributes to the final product. Scrum method is an iterative approach to software development that carries the principle of agile (agility). The Scrum method creates several time blocks called sprints. This method has three artifacts, namely Prioritized product backlog, sprint backlog, and Deliverable.